Comprehensive Review of the Journal of Earth and Marine Technology (JEMT): Insights from a Bloom's Taxonomy Analysis - Muthoni, Odhiambo; Barasa, Nabwire; Wanjala , Kigen (International Journal of Multidisciplinary Approach Research and Science, 2025)
This manuscript provides a comprehensive review of the Journal of Earth and Marine Technology (JEMT), employing Bloom's Taxonomy as a framework for analysis. By categorizing and evaluating the cognitive processes engaged in the journal's articles, the study aims to enhance the accessibility and pedagogical effectiveness of the content. The systematic classification of the JEMT's publications reveals a focus on several key research areas, including Environmental and Geological Assessment, Mining and Resource Estimation Techniques, and Pollution and Waste Management Studies, among others. Using Bloom's Taxonomy, each article is analyzed for the prevalence of cognitive processes such as remembering, understanding, applying, analyzing, evaluating, and creating. This approach adds educational value to the journal and provides insights into the depth of knowledge presented in the articles. The findings indicate a significant emphasis on higher-order cognitive skills, particularly analyzing and creating, aligning with the journal's goal to advance academic and practical understanding of the earth and marine sciences. This study highlights the importance of structured educational frameworks like Bloom's Taxonomy in classifying academic content, which can significantly enhance educational resources' instructional design and utility. The methodology ensures a rigorous, systematic review that contributes to the scholarly community and practical applications in the relevant fields.